math

Simplify Please:

1: (-12xy2z)(3xy)

2: -12xy2z divided by 3xy

3: 2x(2x - 5)

4: -2x(2x-5)

  1. 👍 0
  2. 👎 0
  3. 👁 156
  1. (-12xy^2z)(3xy)
    = (-12*3)(x*x)(y^2*y)(z)
    = -36 x^2 y^3 z

    do the others in like wise...

    1. 👍 0
    2. 👎 0

Respond to this Question

First Name

Your Response

Similar Questions

  1. differential equations

    the directions are to determine whether or not the equation is exact if so then solve it. the question is (x-y^3+ysinx)dx = (3xy^2+2ycosx)dy i solve and i got that it is exact because My is -3y^2+2ysinx and Nx is -3y^2+2ysinx

  2. Math

    How do you factor: 9x^2y^3 - 3x^3y^2 - 15xy i got: 3xy(3xy^2 - x^2y - 5) But how do you factor it further to simplify it? Thx

  3. math

    evaluate 5x^2+3xy-y^2 when x=3 and y=-3

  4. algebra

    sqrt 12x^3 . sqrt 3xy^2 perform the operation and simplify

  1. Algebra

    Are these complete? m^2 + 4mn +4n^2 = (m + 2n)(m+2n) 3x^3y^2 – 3x^2y^2 + 3xy^2 = 3xy(x^2y – xy + y) Thank you

  2. math,algebra,help

    Okay now i need explanation how to do these types of problems. Directions: Divide Problem: (7x^5y^5-21x^4y^4+14x^3y^3)/(7x^3y^3) Realize that you have 7x^3y^3 on the bottom. Now in order to get rid of that, you want to have the

  3. Algebra-Please help

    I'm really stuck on these problems- Simplify 6xy(3xy)^-2? Simplify 12xyz^-2/8x^-2z Thank you

  4. algebra

    add if possible simplify the expression (8x^3y^2+5x^2y^2+6xy^2)+(4x^3y^2-3xy^2)

  1. Algebra - Equations

    If 3xy = 9xz = 12yz = 1, what is the value of x, y, and z? This is just a set of 3 equations: 3xy=1 9xz=1 12yz=1 ⇒(18xyz)^2=1 ⇒ xyz = ± 1/18 ⇒ (x,y,z) = ±(2/3,1/2,1/6) PLEASE TELL ME HOW DID THE SOLUTION CAME UP WITH xyz =

  2. Calculus

    Let 5x^2 - 3xy + 58 = 2y^3 Use implicit differentiation to find y' for the above equation. The first thing I did was move 2y^3 over to that everything is equal to 0. With the -3xy I used the product rule and expanded that. After

  3. Algebra

    I'm having trouble working out these problems. Could someone please assist? with this first one do I factor the x^2 + 3xy - 18y^2 first? x - 3y * x^2 + xy - 30y^2 / x^2 + 3xy - 18y^2 3a^3b^2 * 4a^2 + 2ab + b^2 8a^3 - b^3 12ab^4 3y

  4. Algebra

    A few questions on simplifying rational expressions... 1). 15x^2/10x this simplifies to 3x^2/2 according to my book. But I would think it should be 3/2x since x^2-x=x. Why not? 2). Simplify 3xy/xy+x. How come the (xy)'s don't

You can view more similar questions or ask a new question.